Representasi Pekerja Wanita dalam Serial Drama Hope: Kitai Zero no Shinnyu Shain - Nabila Vina Fairuzzahra; Susy Ong (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2020)
Gender inequality has been an issue in Japanese employment. This issue is then being reflected by media in Japan through drama series such as Hope: Kitai Zero no Shinnyu Shain. Hope: Kitai Zero no Shinnyu Shain told about a rookie worker and his comerades whom tried so hard to work in trading company. This research aimed to identify and explain how female workers were represented in Hope: Kitai Zero no Shinnyu Shain drama series through the characterization of Kazuki Akane and Shiraishi Ryoko. This research is qualitative descriptive research. To analyze data, this research used semiotic approach by Roland Barthes. The result showed that female workers in the drama series were represented as 1) ones whose main role gender was in domestic sphere; 2) ones who supported male counterparts; 3) subordinates who had lower position than male counterparts. Therefore, this representation reflected gender inequality that occured between male workers and female workers.